Levosimendan beyond inotropy and acute heart failure: Evidence of pleiotropic effects on the heart and other organs: An expert panel position paper. (1st November 2016) - Farmakis, Dimitrios; Alvarez, Julian; Gal, Tuvia Ben; Brito, Dulce; Fedele, Francesco; Fonseca, Candida; Gordon, Anthony C.; Gotsman, Israel; Grossini, Elena; Guarracino, Fabio; Harjola, Veli-Pekka; Hellman, Yaron; et al.
Abstract: Levosimendan is a positive inotrope with vasodilating properties (inodilator) indicated for decompensated heart failure (HF) patients with low cardiac output. Accumulated evidence supports several pleiotropic effects of levosimendan beyond inotropy, the heart and decompensated HF. Those effects are not readily explained by cardiac function enhancement and seem to be related to additional properties of the drug such as anti-inflammatory, anti-oxidative and anti-apoptotic ones. Mechanistic and proof-of-concept studies are still required to clarify the underlying mechanisms involved, while properly designed clinical trials are warranted to translate preclinical or early-phase clinical data into more robust clinical evidence. The present position paper, derived by a panel of 35 experts in the field of cardiology, cardiac anesthesiology, intensive care medicine, cardiac physiology, and cardiovascular pharmacology from 22 European countries, compiles the existing evidence on the pleiotropic effects of levosimendan, identifies potential novel areas of clinical application and defines the corresponding gaps in evidence and the required research efforts to address those gaps. Highlights: Levosimendan is a positive inotrope with vasodilating properties. It is indicated for decompensated heart failure with low cardiac output. Levosimendan bears pleiotropic effects beyond inotropy including organoprotection. Therefore, it may be beneficial in conditions beyond decompensated heart failure. Further trials are needed to explore potential translation into clinical practice.